2018
DOI: 10.1590/0102-33062018abb0143
|View full text |Cite
|
Sign up to set email alerts
|

Are native bees and Apis mellifera equally efficient pollinators of the rupestrian grassland daisy Aspilia jolyana (Asteraceae)?

Abstract: Most angiosperms rely on animals for pollination, and insects, especially bees, are the most frequent pollinators. Many native Neotropical plants are frequently visited by the invasive honeybee (Apis mellifera), but its role in the pollination of these plants has been little investigated. We assessed the contribution of various floral visitors, including native bees and the honeybee, on the pollination of a generalist rupestrian grassland daisy, Aspilia jolyana (Asteraceae), in Serra do Cipó, Espinhaço Mountai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…These authors suggested that, in general, secondary pollinators correspond to the ancestral pollinator of related species and may be linked to signals of different pollination syndromes in the same flower. Even though hummingbirds are always cited as a more efficient pollinator, they can also act as a secondary pollinator of, or even an opportunistic visitor to, bee‐pollinated flowers, as observed for Aspilea jolyana (Maruyama et al ., ) and some Vochysiaceae species (Oliveira, ).…”
Section: Discussionsupporting
confidence: 77%
“…These authors suggested that, in general, secondary pollinators correspond to the ancestral pollinator of related species and may be linked to signals of different pollination syndromes in the same flower. Even though hummingbirds are always cited as a more efficient pollinator, they can also act as a secondary pollinator of, or even an opportunistic visitor to, bee‐pollinated flowers, as observed for Aspilea jolyana (Maruyama et al ., ) and some Vochysiaceae species (Oliveira, ).…”
Section: Discussionsupporting
confidence: 77%
“…Our study is one of a handful that looks at the effect of non-native invasive organisms on pollinator effectiveness (e.g. Sinu et al, 2017;Maruyama et al, 2018;Jaca et al, 2019b). Here, pollination effectiveness of vertebrate pollinators appeared to be compromised by the presence of invasive non-native ants, shown by the decrease of flower visitation rates in presence of ants.…”
Section: Discussionmentioning
confidence: 94%
“…The behavior of these bees as floral visitors is because they are opportunists rather than specialists, exploiting those available resources to the maximum with high density (Kleinert & Giannini, 2012). A. mellifera, for example, shows preference for Asteraceae plants and especially those that show mass flowering as candeia species (Maruyama et al, 2018). The preference for Asteraceae flowers in Cerrado biome has already been observed and may be related to the great diversity of species of this family in different areas (Mota et al, 2018).…”
Section: Resultsmentioning
confidence: 97%